CYP 2D6*4 polymorphism in Polycythemia vera patients in Turkish population - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2018)
Objective: Many studies have shown the association of susceptibility to several cancers with gene encoding enzymes' polymorphisms which engage in xenobiotics' biotransformation. In this study, the main purpose is to search the relation between cytochrome P450 (CYP) 2D6* 4 polymorphisms and Polycythemia vera (PV) incidence in Turkish population. Materials and Methods: In this research article, 80 Polycthemia vera (PV) cases and 76 control samples have been used for the analysis of CYP 2D6* 4 polymorphism. The research has been performed by the methods of polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP). Results: As a result, when patients and controls were compared in terms of CYP 2D6* 4 poor metabolizer (PM) and heterozygous extensive metabolizer (HEM) genotype frequency, it has been found that the patients have 1.35% PM and 32.43% HEM frequency, and controls have 2.63% PM and 21.05% HEM frequency. The correlation between the results of CYP 2D6 genotype analysis and the risk of disease in patients and controls was examined. We found that PM, HEM and extensive metabolizer (EM) genotypes were unrelated with the risk of PV (OR 0.51, 95% CI 0.04-5.71, OR 1.80, 95% CI 0.86-3.75,chi(2) 1.93, P: 0.164, OR 0.61, 95% CI 0.30-1.24, chi(2) 1.40, P: 0.235). Conclusion: Our results suggested that the CYP 2D6* 4 polymorphism, in the studied population, does not play an important role in PV etiology.
Keywords: Cytochrome P450 2D6; Genetic polymorphism; Polycythemia vera (PV); ACUTE LYMPHOBLASTIC-LEUKEMIA; CYTOCHROME-P450 2D6; GENETIC POLYMORPHISMS; MYELOPROLIFERATIVE DISORDERS; DRUG-METABOLISM; LUNG-CANCER; SUSCEPTIBILITY; GSTM1; DEBRISOQUINE; GSTT1